IMPLIKASI PARIS AGREEMENT 2015 TERHADAP KEBIJAKAN PEMERINTAH INDONESIA DI SEKTOR ENERGI DALAM MITIGASI PERUBAHAN IKLIM DI INDONESIA (KAJIAN PENGGUNAAN ENERGI BATUBARA DALAM PEMBANGUNAN DI INDONESIA) - Nasution, Syafira Yasmin; Deliana, Evi; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The ratification of an international agreement has implications for the obligation for the state to fulfill the commitment from the results of the ratification. In this case, Indonesia which has ratified the Paris Agreement 2015 has an obligation to adjust domestic policies to conform to the commitments in its Nationally Defined Contribution (NDC) document. The implications referred to in this study are the implications for policies in the energy sector in climate change mitigation efforts. Considering that the Indonesian Government issued electricity energy policies that have a negative impact on climate change mitigation efforts that are in accordance with their commitments.The type of research carried out can be classified by normative-juridical research where this research is conducted on the level of vertical and horizontal synchronization, toexamined the extent of which written positive laws that are harmonious. In this study, the data sources used were secondary data with primary, secondary, and tertiary legal materials carried out by means of library research.From the results of the research obtained, first, the implication of the Paris Agreement 2015 on energy sector policies in Indonesia is the existence of coordination and policy coherence in the energy sector by related institutions. However, the Indonesian Government still has difficulty in adjusting Indonesia's energy needs for national development with efforts to mitigate climate change in the energy sector. This has caused a lack of efforts by the Government to mitigate climate change in the energy sector. Secondly, mitigation efforts through the energy sector have been incorporated into the National Action Plan for Greenhouse Gases with commitments before the Paris Agreement 2015. There has been no review of these mitigation efforts causing Indonesia's commitment in the Paris Agreement 2015 to have no implications for mitigation efforts through the National House Gas Action Plan.Keyword : Paris Agreement 2015-Climate Change Mitigation-Indonesia Energy Sector Policy